2018
DOI: 10.1093/eurheartj/ehy188
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of delta-like 1 homologue accelerates fibroblast–myofibroblast differentiation and induces myocardial fibrosis

Abstract: These findings are the first to demonstrate an inhibitory role of Dlk1 of cardiac fibroblast-to-myofibroblast differentiation by interfering with TGFβ/Smad-3 signalling in the myocardium. Given the deleterious effects of continuous activation of this pathway, we propose Dlk1 as a new potential candidate for therapy in cases where aberrant TGFβ signalling leads to chronic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 27 publications
(48 reference statements)
7
60
3
Order By: Relevance
“…In the adult bone marrow DLK1 mRNA expression is detected by PCR, but with a clear inter-donor variation [32]. Previous studies have shown, that DLK1 is largely absent in the human heart [19], but a very recent study suggests that DLK1 is expressed in adult cardiomyocytes and fibroblasts [33]. This may however be debatable as we have unpublished data demonstrating that DLK1 is only expressed in cells residing in the adult peri-/epicardium, and not within the myocardium itself.…”
Section: Mesodermal Tissuesmentioning
confidence: 97%
See 1 more Smart Citation
“…In the adult bone marrow DLK1 mRNA expression is detected by PCR, but with a clear inter-donor variation [32]. Previous studies have shown, that DLK1 is largely absent in the human heart [19], but a very recent study suggests that DLK1 is expressed in adult cardiomyocytes and fibroblasts [33]. This may however be debatable as we have unpublished data demonstrating that DLK1 is only expressed in cells residing in the adult peri-/epicardium, and not within the myocardium itself.…”
Section: Mesodermal Tissuesmentioning
confidence: 97%
“…Pancreas [19,26,28,29] ------------------Prostate [30,31] Liver [19,26,137] Lung [19] Mesoderm Bone [19,32] --------Heart (unpublished, [33])…”
Section: Pre-natalmentioning
confidence: 99%
“…Moreover, several other miRNAs that were in higher abundance in CMC db/db -derived EVs have been shown to have beneficial actions. For example, the levels of miR-15a, mi339–5p, and mi-370 were higher in EVs derived from CMC db/db cells, and these are thought to be involved in tissue regeneration or fibrosis [37, 51, 53]. That these in vitro measures of cell competence do not equate to in vivo efficacy is an important outcome of this study that merits further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…TGF-β1 is a powerful chemokine for monocytes and broblasts [30]. As well as, it can increase the proliferation ability of broblasts, promote their secretion of extracellular matrix such as collagen and bronectin [31]. TGF-β1 can induce broblasts phenotype Transformation to myo broblasts phenotype, characterized by high synthesis of α-SMA, causing matrix contraction and participating in accelerating the extracellular matrix deposition [32].…”
Section: Discussionmentioning
confidence: 99%